Analysis of international trade data : correlating Chinese economic influence with Chinese United Front influence in Oceania - Ng, Man Chun (Nanyang Technological University, 2021)
China is a rising power on the world stage with growing economic and political influence. This influence is particularly felt in Australia and in New Zealand. United Front work is a key aspect of Chinese political influence abroad, particularly after Chinese president Xi Jinping’s rise to power. United Front work is difficult to track, and a survey over all countries is extremely challenging, but Chinese economic influence in each and every country can be measured easily using readily available trade and investment data. This paper finds a significant correlation between the economic influence of China and United Front work. It also highlights particular economic influence indicators that can predict particular United Front influence indicators. The paper thus provides a way to systematically predict United Front influence in many countries by analyzing commodity trade and Chinese investment data. More research can be done, however, in broadening the scope of this project and in improving data quality.